Pertumbuhan Ekonomi dan Nilai Tukar Barter Sektor Pertanian - Pantjar Simatupang (Pusat Sosial Ekonomi dan Kebijakan Pertanian, 1992)
This paper develops a theoretical framework for the dynamics of the agricultural barter terms of trade using both mathematical and graphical analysis. The analysis shows that the agricultural barter terms of trade tends declining as the economy growing. This declining trend is due to the fact that the demand for agricultural product is inelastic with respect to real income changes. The declining trend of the agricultural barter terms of trade is also generally enhanced by the government interventions which biased toward the production of agricultural product, consumers and industrial sector development. Moreover, the assymmetrical bargaining power between the agricultural and the non-agriculture sectors further induces the declining trend of the agricultural barter terms of trade.